Faktor yang memengaruhi keterampilan penalaran matematis di sekolah dasar: systematic literature review - Zulfa Jihan Hanifa; Retno Winarni; Anesa Surya (Universitas Sebelas Maret, 2023)
Mathematical reasoning skills are one of the most important skills mastered to support the 21st century. The purpose of this research is to systematically search for literature on factors that affect the ability of mathematical reasoning in elementary schools. Searched literature for journal papers published in the 2013-2023 period. The literature criteria used are articles that specifically discuss factors that affect mathematical reasoning skills. According to the results of the search, 4 selected articles that meet the requirements. The review shows that mathematical reasoning abilities are affected positively and significantly by initial knowledge and self-accusations. Therefore, teachers need to develop self-efficacy and early knowledge to support the ability of mathematical reasoning. The conclusion of the study can be used as a reference for further research. As for the practical implications, students are expected to increase self-efficacy and develop their initial abilities so that their reasoning skills also increase., By increasing the ability of mathematical reasoning, the purpose of learning can also be achieved.